Conservatoires in society: Institutional challenges and possibilities for change. (July 2016) - Tregear, Peter; Johansen, Geir; Jørgensen, Harald; Sloboda, John; Tulve, Helena; Wistreich, Richard
Educational sociologists and philosophers have long recognised that educational institutions play a significant role in shaping as well as supporting societal norms. In the face of growing global social, political, and environmental challenges, should conservatoires be more overt in expressing a mission to sustain and improve the societies in which they are located? In times of ever-increasing scepticism emanating from governments and the broader populace alike about the efficacy of public spending, if not the public sphere itself, this essay suggests it is both timely and necessary for conservatoires to reconsider, reinvigorate and re-articulate their capacity to contribute to broader social goods. Drawing on the authors' professional experience as well as current literature and debates, the essay is both deliberately provocative and open-ended, articulating a number of points of departure that institutions might consider in addressing the challenge of maintaining and exercising their relevance to broader society.